Un edificio di Bohdan Lachert e Józef Szanajca a Varsavia - Rossari, Augusto (Studi e ricerche di storia dell'architettura, 2025)
The article examines the work of the two Polish architects, located in Warsaw, framing it in the cultural climate of the period (1924-1939), characterized by the emergence of the avant-garde in Europe. In Poland, the liberation of architects from traditional forms occurs through knowledge of European experiences conveyed by associations such as Blok and Praesens and their magazines which open up new perspectives. Lachert and Szanajca, both members of Block and Praesens, developed the elements of the modernist lexicon in the house on Katowicka Street. The final part of the article takes a look at Lachert’s professional and university activities at the Warsaw Polytechnic after Szanajca’s death.